Quality of Care Received by Children from 1 to 23 Months: Realities in The City of Antananarivo - Fidiniaina Mamy Randriatsarafara; Domoina Zafindrasoa Rakotovao-Ravahatra; Lantonirina Ravaoarisoa; Ando Faramalalatiana Rafanomezantsoa; Jean De Dieu Marie Rakotomanga; Vahiniarison Dieudonné Randrianarimanana (International Journal of Public Health Science (IJPHS), 2018)
Children's health depends on the proper care they receive from their mothers. This study aims to describe the quality of care received by children from 1 to 23 months in the city of Antananarivo. This is a cross-sectional and analytical study for a period from December 2016 to April 2017 in the city of Antananarivo which is the capital of Madagascar. The study population was made up of 420 mother-child dyads living in the city of Antananarivo. Regarding the care received by children, 47.6%, 95% Confidence Interval (CI) [42.8–52.4] benefit from quality nutrition care, 92.3%, 95% CI [89.8-94.8], have a social care and 45.5%, 95% CI [40.9–50.5] receive health care. The hygiene of life 66.4%, 95% CI [61.6–70.6] and the body hygiene 35.3%, 95% CI [30.6–39.8] improve as the child grows up. The care received by children was complete for the five types in 7.6%, 95% CI [5.1–10.1].  With regard to the profile of the mother, mothers under the age of 18 (OR=3.25, 95% CI [1.07-9.46]) and those who are single (OR=3.47, 95% CI [1.24-9.35]) offer more acceptable care to their infants. Infant care depends on the socio-economic and demographic profile of the mother. Thus, it is important to strengthen the communication strategy on infant first aid gestures and mothers' education on childcare.